The Importance of a Wide Interaction Between Universities and Innovation Habitats - Maldonado, Bruno Teixeira (2020)
As institutions focused on teaching and research, universities play a key role in creating and developing the knowledge and technology needed for innovation activities. Given the importance of these elements for socioeconomic development, the interaction between the university and the business sector become essential. However, given their specificities and the different natures of each, there are a number of obstacles to the development of this interaction. The aim of this paper is to investigate how it is possible to overcome such obstacles in the current context of the national innovation system, supported by the bibliographical study of the theme, the triple helix model and the innovation habitats. Finally, the study emphasized the importance of innovation habitats to support this interaction, in order to promote the interaction of triple helix agents, filling the institutional gaps between them, to effect an innovation environment.